Higher Plant-Derived Biostimulants: Mechanisms of Action and Their Role in Mitigating Plant Abiotic Stress - Sara Esperanza Martínez-Lorente; José Manuel Martí-Guillén; María Ángeles Pedreño; Lorena Almagro; Ana Belén Sabater-Jara (MDPI AG, 2024)
Modern agriculture is being challenged by deteriorating edaphoclimatic conditions and increasing anthropogenic pressure. This necessitates the development of innovative crop production systems that can sustainably meet the demands of a growing world population while minimizing the environmental impact. The use of plant biostimulants is gaining ground as a safe and ecologically sound approach to improving crop yields. In this review, biostimulants obtained from different higher plant sources are presented under the term higher plant-derived biostimulants (hPDBs). Their mechanisms of action regulate physiological processes in plants from germination to fructification, conditioned by responses induced in plant mineral nutrition and primary metabolism, specialized metabolism, photosynthetic processes, oxidative metabolism, and signaling-related processes. The aim of this review is to collect and unify the abundant information dispersed in the literature on the effects of these biostimulants, focusing on crops subjected to abiotic stress conditions and the underlying mechanisms of action.